Development and performance assessment of a novel combined power system integrating a supercritical carbon dioxide Brayton cycle with an absorption heat transformer. (1st January 2022) - Tang, Junrong; Zhang, Quanguo; Zhang, Zhiping; Li, Qibin; Wu, Chuang; Wang, Xurong
Highlights: A combined system based on the sCO2 cycle is proposed for power generation. An absorption heat transformer is employed to upgrade the sCO2 cycle waste heat. The regenerative effect of the sCO2 cycle is enhanced in the proposed system. The proposed system can improve thermodynamics and economy by 4.96% and 3.66%. Abstract: This study aims to investigate the system performance enhancement brought by an absorption heat transformer (AHT) on the supercritical carbon dioxide (sCO2 ) Brayton cycle. In the proposed sCO2 /AHT system, the AHT cycle serves as a bottoming cycle to upgrade the energy level of the waste heat in the sCO2 system, producing high-quality thermal energy output to preheat the CO2 at the main compressor outlet. System performance is evaluated through the established and validated model. The variation trends of system performance with four key parameters are determined from the parametric analysis. Moreover, optimization and comparative analysis are performed for the sCO2 system, sCO2 /ORC system and sCO2 /AHT system. The results suggest that the sCO2 /AHT system shows the best system performance. The exergy efficiency of the proposed system is 64.013%, which is 4.96% and 1.87% higher than that of the sCO2 system, sCO2 /ORC system. The total product unit cost of the proposed system is 18.903/GJ, which is 3.66% and 2.24% lower than that of the other two systems. Exergy analysis indicates that compared with the sCO2 system, the proposed system can effectively reduce the exergy destructions in the pre-cooler (4.97 MW to 1.32 MW) and get a strengthened regeneration effect for the sCO2 cycle.